Daisy May - Jean Ure
A rags to riches story of a young orphan who becomes a famous actress. Daisy is brought up in a foundling's hospital in Victorian times. At ten she is sent into service as a skivvy at the Dobell Academy, where she watches all the pupils learning how to be young ladies, wearing fine clothes and learning how to read, write and...dance. Daisy dreams of being like them one day and painstakingly teaches herself to read with the help of one kind teacher. A wonderful unashamedly sentimental rags-to-riches story which young readers from 7 and upwards will adore.